Development of an AAV9-RNAi-mediated silencing strategy to abrogate TRPM4 expression in the adult heart - Rebekka Medert; Andreas Jungmann; Staffan Hildebrand; Martin Busch; Dirk Grimm; Veit Flockerzi; Oliver J. Müller; Patrick Most; Dagmar Schumacher; Marc Freichel (Pflügers Archiv - European Journal of Physiology, 2021)
The cation channel transient receptor potential melastatin 4 (TRPM4) is a calcium-activated non-selective cation channel and acts in cardiomyocytes as a negative modulator of the L-type Ca 2+ influx. Global deletion of TRPM4 in the mouse led to increased cardiac contractility under β-adrenergic stimulation. Consequently, cardiomyocyte-specific inactivation of the TRPM4 function appears to be a promising strategy to improve cardiac contractility in heart failure patients. The aim of this study was to develop a gene therapy approach in mice that specifically silences the expression of TRPM4 in cardiomyocytes. First, short hairpin RNA miR30 (shRNA miR30 ) sequences against the TRPM4 mRNA were screened in vitro using lentiviral transduction for a stable expression of the shRNA cassettes. Western blot analysis identified three efficient shRNA miR30 sequences out of six, which reduced the endogenous TRPM4 protein level by up to 90 ± 6%. Subsequently, the most efficient shRNA miR30 sequences were delivered into cardiomyocytes of adult mice using adeno-associated virus serotype 9 (AAV9)-mediated gene transfer. Initially, the AAV9 vector particles were administered via the lateral tail vein, which resulted in a downregulation of TRPM4 by 46 ± 2%. Next, various optimization steps were carried out to improve knockdown efficiency in vivo. First, the design of the expression cassette was streamlined for integration in a self-complementary AAV vector backbone for a faster expression. Compared to the application via the lateral tail vein, intravenous application via the retro-orbital sinus has the advantage that the vector solution reaches the heart directly and in a high concentration, and eventually a TRPM4 knockdown efficiency of 90 ± 7% in the heart was accomplished by this approach. By optimization of the shRNA miR30 constructs and expression cassette as well as the route of AAV9 vector application, a 90% reduction of TRPM4 expression was achieved in the adult mouse heart. In the future, AAV9-RNAi-mediated inactivation of TRPM4 could be a promising strategy to increase cardiac contractility in preclinical animal models of acute and chronic forms of cardiac contractile failure.

Decreased contractility due to energy deprivation in a transgenic rat model of hypertrophic cardiomyopathy - Mark Luedde; Ulrich Flögel; Maike Knorr; Christina Grundt; Hans-Joerg Hippe; Benedikt Brors; Derk Frank; Uta Haselmann; Claude Antony; Mirko Voelkers; Juergen Schrader; Patrick Most; et al. (Journal of Molecular Medicine, 2009)